Into the wild: uncertain frontiers and sustainable human–nature interactions - Patterson, Jennifer (Frontiers in Sociology, 2024)
In this article I examine health and illness interactions between people and nature. I demonstrate how, in the anthropocentric Global North political economies h a v e historically cultivated a separation of people from nature. T h i s changes t h e i r ethical and sustainable premises from nature being a place of renewal identified with people as human animals. Moreover, culminating in a resource-driven consumer culture influencing climate change has led to an ability to deal with instability, increasing forms of illness in people and the planet. As I investigate mainstream and countercurrent ideas with respect to healthy interactions alongside physical, mental and emotional harms, I argue that the separation of people and nature is an eco-anomie, a damaging relational autoimmune disorder justifying the need for a new earth-centered paradigm.